Aridification du climat régional et remontée de la limite inférieure du cèdre de l'Atlas (Cedrus atlantica Manetti) aux confins de la plaine de Midelt (Maroc) - Mustapha Rhanem (Physio-Géo)
The Atlas cedar (Cedrus atlantica Manetti), a phanerophyte, needs some humidity according to seasons as well as certain phases of its development. Very spontaneously widespread in Morocco, it has a great ecological, floristic, socio-economic and heritage value. For a long time, this precious species has been very well adapted to its highland Mediterranean environment and has no sanitary problems. However, since the early 1980s, it is affected by a worrying diffuse or concentrated decay that provokes a recession of its population. The dieback reaches abnormally high proportions in some of the Midelt forested regions, in Middle and High Atlas. The first signs are shown by attacks on isolated trees or clumps of trees covering various areas. This phenomenon can be generalized in Aït-Oufella woodlands, on the southern edge of the central Middle Atlas, near the Midelt arid plain, where mortality is locally very high. But in most cases it is concentrated on the lower limit of the species repartition area.A review of rainfall and temperature measured from 1957 to 2005 at the Midelt meteorological station – that is representative of the semi-arid environment prevailing at the lower limit of the cedar repartition area on the Middle Atlas Moulouya slope – allows to formulate the following hypothesis: failings are caused by rain deficit combined with an increasing of temperatures, in association with several droughts during the 1982-2005 period.During this period, climatic conditions had a negative impact on cedar vitality resulting in the death of numerous trees. The effects of drying are particularly perceptible in the areas where the initial conditions were already far from the species ecological optimum. Disappearance of ecological niches in the lowest sectors of the species repartition area has provoked an ascent of the lower altitudinal limit from 1800 m to 2000 m. The Atlas cedar was gradually replaced by holm oak stands (Quercus ilex L.) with prickly juniper (Juniperus oxycedrus L.).For different reasons, all related to aspect (sunlight, diurnal topoclimatic differences, west wind snow deflation), cedar decline is more important on the east slopes of small valleys flowing from the Middle Atlas down to Midelt plain.